Technopopulism: The Emergence of a Discursive Formation - Marco Deseriis (tripleC: Communication, Capitalism & Critique)
This article contends that technopopulism is a discursive formation that emerges from the convergence of two preexisting discourses: populism and technolibertarianism. Whereas these discourses are historically distinct the 2008 financial crisis and the 2011 wave of struggles have precipitated the political conditions for their intersection and hybridization. Such convergence produces both tensions and possibilities. On the one hand, technopopulism engenders a radically participatory model of democracy, which is ultimately anti-institutional as citizens cooperate and engage in sophisticated decision-making without the mediation of professional politicians. On the other hand, the more successful technopopulist parties—at least in the electoral arena—are all led by charismatic leaders who synthesize the positions that emerge from the netroots to mobilize them against the establishment. These two seemingly contradictory aspects precipitate in two variants of technopopulism: a leaderless-technocratic variant, which is derived from the open source mode of governance and from early experiments of the Global Justice Movement in networked self-government; and a leaderist-populist variant, which is more strictly focused on the electoral competition as an intrinsically reductive and thus hegemonic practice. The article concludes with a reflection on the discursive complementarity of these two variants and on the political tensions and challenges technopopulism faces in the current phase.